Lessons learned during the internship: experiences of recent medical graduates - Osornio Castillo , Leticia; Peralta Cortes, Elias Nain; Méndez Cruz , Adolfo René (Spanish Journal of Medical Education, 2025)
Background: To produce graduates of the highest quality, ongoing evaluation of the educational process is required. The undergraduate rotating internship is a fundamental stage in the training of general practitioners; therefore, assessing the learning they acquired will allow us to determine whether the objectives of the curriculum for this program are being achieved and what aspects need to be strengthened. The objective was to analyze the learning acquired during the undergraduate rotating internship from the perspective of graduates of the Medical and Surgery program and its relationship to the program’s objectives and professional profile. Methods: This was a qualitative research study, with the participation of 15 graduates of the Medical and Surgery program at FESI-UNAM. After signing an informed consent form, they were conducted in a semi-structured individual interview. Results: The qualitative analysis grouped the information into six topics: 1) Development of critical thinking and clinical reasoning in rotations, 2) The hospital as a favorable environment for teamwork and effective communication, 3) The internship and the different scenarios of medicine, 4) Self-regulated learning during the internship, 5) Challenges of the internship: adaptation to complex environments, and 6) The internship as an essential academic cycle in the curriculum. Conclusions: The graduates of the Medical Surgeon program from the Iztacala School of Higher Studies showed a positive appreciation of the rotating internship, however, they consider necessary modifications in the respect for the staff of some health institutions and in the functions of the interns, in accordance with the established regulations (Draft Mexican Official Standard PROY-NOM-033-SSA-2023), to guarantee high quality training without compromising the physical and mental well-being of future physicians.